4-[2-O-11Z-Octadecenoyl-β-glucopyranosyl]-4, 4′-diapolycopene-4, 4′-dioic acid and 4-[2-O-9Z-hexadecenoyl-β-glucopyranosyl]-4, 4′-diapolycopene-4, 4′-dioic acid: new C30-carotenoids produced by Methylobacterium. Issue 21 (20th May 2015) - Osawa, Ayako; Kaseya, Yui; Koue, Nao; Schrader, Jens; Knief, Claudia; Vorholt, Julia A.; Sandmann, Gerhard; Shindo, Kazutoshi
Graphical abstract: Abstract: During the course of screening for antioxidative carotenoids from bacteria, we isolated two novel C30 carotenoids, 4-[2- O -11 Z -octadecenoyl-β-glucopyranosyl]-4, 4′-diapolycopene-4, 4′-dioic acid (1 ) and 4-[2- O -9 Z -hexadecenoyl-β-glucopyranosyl]-4, 4′-diapolycopene-4, 4′-dioic acid (2 ), from Methylobacterium strains. These compounds possessed the common structure 'β-d -glucosyl 4, 4′-diapolycopene-4, 4′-dioic acid', while the fatty acid attached at the C-2 position of glucose differed. In the singlet oxygen ( 1 O2 ) quenching model, both1 and2 exhibited potent antioxidative activities (IC50 : 3.2 and 3.6 μM, respectively).